Effect of Wolbachia wAlbB on a positive-sense RNA negev-like virus: a novel virus persistently infecting Aedes albopictus mosquitoes and cells. (17th December 2019) - Bishop, Cameron; Parry, Rhys; Asgari, Sassan
Abstract : The Aedes aegypti mosquito is the primary vector of several medically important arboviruses. The endosymbiotic bacterium, Wolbachia pipientis, has emerged as a means of blocking transmission of arboviruses such as dengue and Zika viruses. One Wolbachia strain that has shown potential in field trials is w AlbB, a naturally occurring Wolbachia strain of the Asian tiger mosquito Aedes albopictus . When transinfected into Ae. aegypti, w AlbB exhibits strong virus inhibition. In addition to modulating arboviruses, Wolbachia also modulates some insect-specific viruses. Here, we explored the effect of Wolbachia on the virome of the Ae. albopictus cell line Aa23 naturally infected with w AlbB and also a stably transinfected recipient Ae. aegypti cell line (Aag2. w AlbB). RNA sequencing and bioinformatic analysis on both cell lines revealed an 11 kb genome of a single-stranded positive-sense RNA negev-like virus related to the recently proposed negevirus taxon. We denoted this novel virus as Aedes albopictus negev-like virus (AalNLV). Tetracycline clearance of Wolbachia from Aa23 cells did not significantly affect AalNLV levels, while in Aag2. w AlbB cells, a significant increase in virus genome RNA copies was observed. We further investigated the inhibitory effect of w AlbB on AalNLV and another positive-sense RNA virus, cell fusing agent virus, which is present in Aag2 cells and known to be suppressed by Wolbachia. w AlbB suppressed both viruses, with the effect on AalNLV being more striking. The findings from this study further supplement our understanding of the complex interaction between Wolbachia, host and virome.